Growth Attenuation Therapy: Views of Parents of Children with Profound Cognitive Impairment - Kerruish, Nikki (Cambridge quarterly of healthcare ethics, 2016)
The “Ashley treatment” has provoked much debate and remains ethically controversial. Given that more children are being referred for such treatment, there remains a need to provide advice to clinicians and ethics committees regarding how to respond to such requests. This article contends that there is one particularly important gap in the existing literature about growth attenuation therapy (GAT) (one aspect of the Ashley treatment): the views of parents of children with profound cognitive impairment (PCI) remain significantly underrepresented. The article attempts to redress this balance by analyzing published accounts both from parents of children who have received GAT and from parents who oppose treatment. Using these accounts, important points are illuminated regarding how parents characterize benefits and harms, and their responsibilities as surrogate decisionmakers. This analysis could contribute to decisionmaking about future requests for GAT and might also have wider relevance to healthcare decisionmaking for children with PCI.